Payments and Securities Clearance and Settlement Systems in Bolivia - Centro de Estudios Monetarios Latinoamericanos; World Bank (Mexico, D.F.: Centro de Estudios Monetarios Latinoamericanos and the World Bank, 2013)
This report covers the Western Hemisphere payments and securities settlement forum center for Latin American monetary studies and focuses on several issues. The first section covers economic and financial markets overview of Belarus. This section covers the financial sector, capital markets, and major trends in the payments systems. The second section covers institutional aspects such as the general legal framework, role of financial institutions, market structure and regulation, and the role of the securities regulatory. The third section covers the payment media used by non financial entities. The fourth section describes payments, such as inter-bank exchanges and settlement circuits. The fifth section touches on securities, market structure and trading. While the sixth and seventh section cover the topic of settlement circuits for government and corporate securities. The report concludes with discussion on the role of the central bank in clearance and settlement systems and well as the supervision of such systems.